The effectiveness of music interventions in exam anxiety reduction among university students –systematic review - Issa Abuiram; Noor Hassline Mohamed; Muna Ahmead; Praneetha Palasuberniam; Heba Awadallah; Elpidia Juli (Bentham Open., 2025)
Exam anxiety is a common global issue for university students; it is associated with poor academic success and self-confidence. This review investigates the potential benefits of music for reducing anxiety. Following the PRISMA guidelines, this review incorporated experimental studies published in English between January 2019 and January 2024, identified through systematic searches of four databases: PubMed, Cochrane Library, ScienceDirect, and Wiley Online Library. Studies meeting the predetermined inclusion criteria underwent methodological quality assessment using the Joanna Briggs Institute (JBI) checklists for randomized controlled trials and quasi-experimental studies. A review of ten studies, selected from an initial 453, found that music interventions significantly reduced exam anxiety in nine of them. This reduction was evidenced by statistically significant decreases in anxiety scores across various assessment tools (STAI, IEF, VSAF, EAS) and improvements in physiological vital signs. Discussion: Music interventions are effective in reducing exam anxiety, a non-pharmacological approach that complements existing strategies. This benefit is supported by self-reported and physiological measures, highlighting music's versatility for anxiety management, even in brief applications. It also contributes to student well-being and academic success, aligning with Sustainable Development Goal 3. Further research on music types and individual responses is needed for optimal results. Exposure to 15 minutes of instrumental classical music before an exam can significantly lower student anxiety. This finding suggests an effective and low-cost way for universities to support student well-being.